Implementasi Perlindungan Hukum Terhadap Pihak Yang Lemah Atas Merger Perseroan Ditinjau Dari Aspek Finansial - Litha Febian Anggi Pratama; Erik Edwar Firdiyansyah; Sumriyah Sumriyah (Universitas Katolik Widya Karya Malang, 2023)
Merger or in English it is called Merger is one of the methods carried out as part of restructuring in addition to various other forms. Merger is a new trend carried out by companies that are in the developing stage to develop a company to expand the company's target market. In carrying out a company merger, of course there is a company that is more dominant and stronger and on the one hand there is a company that is positionally weaker. So that the parties that carry out the merger are two companies that have dominance and a minority that are used to strengthen the company under one umbrella of business entity. If viewed from the financial aspect, the position is divided into two, namely majority shareholders and minority shareholders. . This of course results in unfair business competition so that in overcoming fair business competition in the financial aspect, legal protection must be given to weak parties in terms of Law No. 40 of 2007 concerning Limited Liability Companies, which UUPT provides legal protection minority shares stipulated in Article 37 Paragraph 1, Article 62, Article 126 with the aim of achieving usability, certainty and justice in accordance with legal objectives.